2021
DOI: 10.1101/2021.11.11.468204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MICS1 is the Ca2+/H+ antiporter of mammalian mitochondria

Abstract: Mitochondrial Ca2+ ions are crucial regulators of bioenergetics, cell death pathways and cytosolic Ca2+ homeostasis. Mitochondrial Ca2+ content strictly depends on Ca2+ transporters. In recent decades, the major players responsible for mitochondrial Ca2+ uptake and release have been identified, except the mitochondrial Ca2+/H+ exchanger (CHE). Originally identified as the mitochondrial K+/H+ exchanger, LETM1 was also considered as a candidate for the mitochondrial CHE. Defining the mitochondrial interactome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…In summary, Patron et al (2022) identified a novel mechanism of proteome remodeling in mitochondria, one that is intertwined with the proton gradient and with Ca 2+ cycling and, therefore, with the bioenergetics status of mitochondria. Of note, the Ca 2+ /H + antiporter function of TMBIM5 was confirmed by a recent preprint (Austin et al , 2021) but was partially contradicted in a current study by Zhang et al (2022). Disagreements on the channel activity aside, the latter publication carries intriguing phenotypic data of a mouse TMBIM5 mutant that shows skeletal myopathy and increased perinatal mortality.…”
Section: Figure Critical Function Of Tmbim5 In Coordinating Mitochond...contrasting
confidence: 41%
“…In summary, Patron et al (2022) identified a novel mechanism of proteome remodeling in mitochondria, one that is intertwined with the proton gradient and with Ca 2+ cycling and, therefore, with the bioenergetics status of mitochondria. Of note, the Ca 2+ /H + antiporter function of TMBIM5 was confirmed by a recent preprint (Austin et al , 2021) but was partially contradicted in a current study by Zhang et al (2022). Disagreements on the channel activity aside, the latter publication carries intriguing phenotypic data of a mouse TMBIM5 mutant that shows skeletal myopathy and increased perinatal mortality.…”
Section: Figure Critical Function Of Tmbim5 In Coordinating Mitochond...contrasting
confidence: 41%
“…LETM1-KD H9c2 cells altered Ca 2+ efflux, indicating LETM1-HCX mediated Ca 2+ efflux ( Natarajan et al, 2020 ) whereas another finding showed that LETM1 mediated mitochondrial Ca 2+ regulation is facilitated by a LETM1-KHE activity, modulating the activity of the mitochondrial Na + /H + exchanger (mNHE) eventually affecting NCLX-mediated Ca 2+ efflux ( Austin et al, 2017 ). A recent study demonstrates that MICS1 is the long-sought mitochondrial CHE and interacts with LETM1, modulating its activity ( Austin et al, 2021 ). Irrespective of its individuality, LETM1 has been implicated in interaction with signaling proteins such as MRPL36, BCS1L and CTMP to modulate protein import and assembly in IMM, mitochondrial morphology and metabolism ( Park et al, 2014 ; Li et al, 2019 ).…”
Section: Mitochondrial Transporters/channelsmentioning
confidence: 99%
“…The membrane potential generated by the electron transport chain (ETC), with a negative matrix charge, provides the electrochemical force necessary for positively charged ions, such as Ca 2+ , to enter. Ca 2+ efflux from the mitochondrial matrix occurs through the Na + /Ca 2+ exchanger (NCLX) (11), located in the inner mitochondrial membrane (IMM), and by a Ca 2+ /H + exchanger, which may have been recently identified (12,13).…”
Section: Introductionmentioning
confidence: 99%